Frustration of purpose: comparative analysis, criticism and proposals in the Peruvian legal system - Meza Lazo, Anjana Shanta (2021)
The figure of the frustration of purpose turns out to be interesting, since it puts in check the principle of the pacta sunt servanda, typical of the civil law that would become our legal family. In Peru, this figure is not currently included in the legislation. However, in 2019, a first regulation proposal was presented in article 1372-A of the Preliminary Draft reform of the Peruvian Civil Code, which would show the importance that this figure would be obtaining in the country. For this reason, in this text, we will carry out an analysis on the frustration of purpose from the comparison of legal systems such as English, North American, German, Argentine and Colombian. Likewise, we will analyze the Peruvian case and evaluate the proposal of the Preliminary Draft reform of the Peruvian Civil Code. Finally, we will present our own regulation proposal that aims not only to reformulate what was presented in the Draft Bill, but also aims to be a user guide for those who wish to apply this figure. In our proposal we propose that (i) its application be given in synalagmatic contracts; (ii) that the purpose is expressed in the contract or is undoubtedly understood based on its ordinary or natural purpose; (iii) that the frustration is caused by an extraordinary event; (iv) that a distinction is made between total and partial frustration; (v) that the resolution can be given by sending a resolution notarial letter; and (vi) that only the creditor of the obligation is the one who can claim the frustration of purpose.